POLA PENGEMBANGAN SEKTOR PEREKONOMIAN BERBASIS AGRIBISNIS DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN DI PROPINSI BALI - Hardjono Hardjono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
Bali government has developing plan for non-agriculture economic sectors to support the development of agriculture sector. It aims to supports the growing of various economic productive activities, especially agro-industry activities from the upper sector to downstream sector.The objective of this research are 1) to identify which economic factor is needed to be developed imperatively; 2) which missing factor is needed to be injected by taking advantages from economic sector priority; based on superior comparative value, electric sector, gas and pure water have LQ (Location Quotient) and DLQ (Dynamic Location Quotient) agriculture sector shows superior comparative high LQ 1,154 and high DLQ 2,28; and also low CD (Coefficient of Dispersion) 0,11676 and low SD (Sensitive of Dispersion) 0,45654. Trading sector, hotel and restaurant LQ 1,865 and DLQ 0,53; low CD 0,83254 and very low SD 0,17500; transportation and communication show superior comparative high LQ 1,787 and DLQ 0,32; CD 0,39439 and SD 0,26056. Mining sector, the superior comparative is considered since it has high LQ and low DLQ. Building sector, superior comparative low LQ 0,634 and DLQ 0,61; CD 0,99908 and SD 0,03020; meanwhile finance, rent, and trading service has high LQ 0,847 and DLQ 0,413; CD 0,12581 and SD 0,26708; and service sector high LQ 1,603 and DLQ 3,02 and also for CD 0,09443 and SD 0,19257; which will disappear depends on the market mechanism.